Dietary antioxidant index and hypertension in the Iranian population: a nested case–control study within the Fasa adults cohort study - Mohammad amin Firooznia; Mehran Rahimlou; Eghbal Sekhavati; Mohammadreza Motazedian; Reza Tabrizi; Reza Tabrizi (Frontiers in Nutrition)
IntroductionHypertension (HTN) is a prevalent condition associated with numerous cardiovascular and non-cardiac complications. Lifestyle interventions, including dietary adjustments, offer promising avenues for hypertension management. However, the precise relationship between dietary antioxidants and hypertension risk necessitates further investigation. This study aimed to elucidate the association between the Dietary Antioxidant Index (DAI) and hypertension risk using a nested case–control design.MethodA matched nested case–control study was conducted within the Fasa Adult Cohort Study (FACS), comprising 975 participants aged 35–70 years. Cases (n = 325) were hypertensive patients, while controls (n = 650) were individuals without hypertension, matched for sex and age. Dietary intake was assessed using a validated food frequency questionnaire, and DAI was computed based on standardized intake of antioxidants. Conditional logistic regression models were employed to evaluate the association between DAI and hypertension risk, adjusting for confounding variables.ResultsA significant inverse correlation was observed between DAI and hypertension risk across all models (OR = 0.89; 95% CI = 0.86–0.93, p < 0.001). This association remained robust after adjusting for potential confounders, including BMI, smoking, lipid profile, blood glucose levels, and educational status. In conclusion, higher DAI values were associated with a reduced risk of hypertension, highlighting the potential benefits of antioxidant-rich diets in hypertension prevention.ConclusionThese findings underscore the importance of dietary interventions as a complementary approach to hypertension management.